AB0985 Comparison of two different intra-articular hyaluronic acid compounds for carpo-metacarpal joint osteoartrhitis. (23rd January 2014) - Massarotti, M.; Crotti, C.; Ughi, N.; Uboldi, F.; Belloli, L.; Marasini, B.
Abstract : Background: Carpometacarpal osteoarthritis (CMC OA) is highly prevalent in older adults, and is often unresponsive to medical treatment. Intra-articular hyaluronic acid (HA) has been widely shown to improve pain and function in patients with knee OA and it seems to be a promising therapy also for CMC OA. To date no studies compared the efficacy of different HA compounds in CMC OA. Objectives: To investigate the three-month efficacy of two different HA compounds on pain relief in CMC OA. Methods: Eighty female patients affected by symptomatic CMC OA (aged 65±8 years, mean ± SD) were treated with three once-weekly intra-articular injections of HA (Hyalgan 1ml, MW 500-700 kDalton, or Jointex 1ml, MW 800-1200 kDalton). All subjects met ACR criteria for hand OA and had CMC OA grade 1-4 according to Kellgren and Lawrence on standard X-ray performed within 6 months before the inclusion. Fourty patients (aged 64±8 years, mean ± SD) were treated with Hyalgan while 40 patients (aged 67±8 years, mean ± SD) were treated with Jointex. All the patients were followed for a 3-month period after the last injection. Treatment efficacy was assessed through visual analogue scale (VAS) pain quantification (baseline; 2nd and 3rd injection; one and three months after the last injection). Side effects were recorded. Results: In both groups VAS was significantly reduced after the first injection and reached the slowest score one month after the last injection (Hyalgan: 2nd injection vs baseline, p=0.0019; 3rd injection vs baseline, p<0.0001; 3rd injection vs 2nd injection, p=0.057; Jointex: 2nd injection vs baseline, p=0.0008; 3rd injection vs baseline, p<0.0001; 3rd injection vs 2nd injection, p=0.0096). The efficacy was maintained for all the whole follow-up period (Hyalgan and Jointex: one month vs baseline, p<0.0001; three months vs baseline, p<0.0001 - one month vs 3rd injection, p=n.s.;three months vs 3rd injection, p=n.s.). No significant differences in VAS score were found between the two groups at baseline and during the follow-up period (Hyalgan vs Jointex: baseline 7.05±2.33 vs 7.08±2.07; 3rd injection 4.35±2.85 vs 4.30±2.29; 1month 3.75±2.65 vs 3.25±2.22; 3months 4.23±2.90 vs 4.03±2.56; p=n.s.). Only minor side effects were observed in both treatment groups (mild pain and/or ecchymosis in injection site). Conclusions: Our study supports viscosupplementation with HA as a safe and efficacious approach for symptomatic CMC OA. In our preliminary study no significant differences were found between intra-articular Hyalgan and Jointex for pain relief. Further studies are needed to determine the long-term efficacy and the optimal treatment schedule. Disclosure of Interest: None Declared